Weakening-free polyurethane composite material as well as preparation method and application thereof

By adopting a weak-free polyurethane composite material in the interior of the car and using a three-dimensional mesh crosslinking structure of the high-solid bonding layer of polyurethane, the cost and aesthetics of traditional weakening treatment are solved, and the safe deployment of the airbag and the improvement of the car's performance are achieved.

CN119526870AActive Publication Date: 2025-02-28ANHUI ANLI MATERIAL TECH

Patent Information

Application Number
CN202411706456.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The traditional automotive interior polyurethane leather needs to be weakened in the dashboard airbag area, resulting in increased processing costs, reduced aesthetics, and affects the energy consumption economy and power performance of the car.

Method used

A weak-free polyurethane composite material is used, which includes a polyurethane surface layer, a polyurethane high-solid adhesive layer and a base cloth layer. The polyurethane high-solid adhesive layer reacts with the reactive polyurethane prepolymer and crosslinking agent and filler to form a three-dimensional mesh crosslinking structure, realizing the strength and brittleness of the film, ensuring that overall brittle fracture can occur under the impact of point explosive force.

Benefits of technology

It realizes the safe deployment of the airbag, reduces the weight of the product, improves the energy consumption economy and power performance of the car, and reduces the rear processing cost and improves the aesthetics of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005154626430000091
    Figure BDA0005154626430000091
Patent Text Reader

Abstract

The invention relates to a weakening-free polyurethane composite material as well as a preparation method and application thereof. The weakening-free polyurethane composite material comprises a polyurethane surface layer, a polyurethane high-solid bonding layer and a base cloth layer which are sequentially arranged from top to bottom, wherein the polyurethane high-solid bonding layer is prepared from a polyurethane high-solid bonding layer slurry, and the polyurethane high-solid bonding layer slurry is prepared from the following components in parts by mass: 100 parts of a reactive polyurethane prepolymer, 5 to 10 parts of a cross-linking agent, 20 to 50 parts of a filler and 5 to 10 parts of color paste. According to the polyurethane high-solid bonding layer disclosed by the invention, the reaction type polyurethane prepolymer, the cross-linking agent and the filler react according to a certain proportion to form a three-dimensional network cross-linked structure, so that a leather film has certain strength and brittleness, and the weakening-free polyurethane composite material can generate overall brittle fracture under the impact of ignition force; and safe unfolding of the air bag is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a weakening-free polyurethane composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of the automobile industry, the quality and performance requirements of automobile interior materials are getting higher and higher. Traditional automobile interior polyurethane leather needs to be weakened in the instrument panel airbag area, which not only increases the cost of post-processing, but also affects the aesthetics of the product and leaves a weakening mark. In addition, in order to reduce the weakening mark, traditional automobile interior leather has a high requirement for the thickness of the adhesive layer, which leads to an increase in weight, which in turn affects the energy consumption economy and power performance of the car.

[0003] Although there have been attempts to develop non-weakening polyurethane skin technology for automotive interiors, there are still many problems. For example, although the method of improving solvent-free adhesion can solve the weakening problem to a certain extent, it is difficult to safely deploy large air bags during explosions due to the toughness of the solvent-free skin film. In addition, although the method of using solvent-free skin to bond left-handed polylactic acid base fabric has achieved non-weakening, the polylactic acid material is not resistant to high temperature and ultraviolet radiation, which limits its application in the dashboard area. Summary of the invention

[0004] Based on this, the present invention provides a non-weakening polyurethane composite material and a preparation method and application thereof. The non-weakening polyurethane composite material can undergo overall brittle fracture under the impact of explosive force, thereby ensuring the safe deployment of the airbag.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The present invention first provides a weakening-free polyurethane composite material, which comprises a polyurethane surface layer, a polyurethane high-solid bonding layer, and a base fabric layer arranged in sequence from top to bottom;

[0007] The polyurethane high-solid adhesive layer is prepared from a polyurethane high-solid adhesive layer slurry, and the polyurethane high-solid adhesive layer slurry is prepared from the following components in parts by weight: 100 parts of reactive polyurethane prepolymer, 5-10 parts of crosslinking agent, 20-50 parts of filler, and 5-10 parts of color paste.

[0008] The polyurethane high-solid adhesive layer of the present invention forms a three-dimensional network cross-linked structure by reacting a reactive polyurethane prepolymer with a cross-linking agent and a filler in a certain proportion, so that the film has a certain strength and brittleness, thereby achieving an overall brittle fracture of the non-weakened polyurethane composite material under the impact of the explosive force, thereby ensuring the safe deployment of the airbag.

[0009] As a further improvement of the above scheme of the present invention, the reactive polyurethane prepolymer is an aliphatic isocyanate prepolymer, and its solid content is 100%, and the free NCO content is 4.5%±1%. The reactive polyurethane prepolymer of the present invention is an aliphatic isocyanate prepolymer, and after reacting with a crosslinking agent and a filler, the unreacted isocyanate groups in the reactive polyurethane prepolymer can react with the active hydrogen groups on the base fabric, thereby obtaining a higher bonding strength.

[0010] As a further improvement of the above solution of the present invention, the cross-linking agent is one of aliphatic amine cross-linking agents, acid anhydrides, and polyamides.

[0011] As a further improvement of the above solution of the present invention, the filler is at least one of diatomaceous earth, powdered calcium carbonate, aluminum hydroxide, halogen flame retardant, and phosphorus flame retardant.

[0012] As a further improvement of the above scheme of the present invention, the polyurethane surface layer is prepared from a polyurethane surface layer slurry, and the polyurethane surface layer slurry is prepared from the following components by weight: 150 parts of aliphatic polyurethane resin, 10-50 parts of N,N-dimethylformamide, and 5-10 parts of color paste. It should be noted that in the present invention, there are no special requirements for the aliphatic polyurethane resin, color paste, etc. in the polyurethane surface layer, which can be adjusted according to product requirements, and the color paste can also be selected according to product performance requirements, so it is not specifically limited here.

[0013] As a further improvement of the above solution of the present invention, the base fabric layer is a low-density polyester knitted mesh fabric, and the tear strength of the base fabric layer is 10-25N / 3cm.

[0014] The present invention further provides a method for preparing the aforementioned weakening-free polyurethane composite material, which comprises the following steps:

[0015] S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 10-20 threads, place it at 100-140℃ for 1-2min, and dry it to form a polyurethane surface layer;

[0016] S2. A polyurethane high solid resin slurry is coated on the polyurethane surface layer with a cutter gap of 30-40 wire, and is dried at 110-140 ℃ until semi-dry to form a polyurethane high solid adhesive layer;

[0017] S3. Laminating the base fabric and the polyurethane high-solid adhesive layer with a lamination gap of 60-80 mm, and drying to obtain a weakening-free polyurethane composite material.

[0018] As a further improvement of the above solution of the present invention, the method for preparing the weakening-free polyurethane composite material further comprises the following steps:

[0019] S4. After coating the water-based polyurethane slurry on the surface of the non-weakening polyurethane composite material with a roller coating process, treating it at 130-160° C. for 2-5 minutes, and drying it, a surface treatment layer is formed on the surface of the non-weakening polyurethane composite material.

[0020] As a further improvement of the above scheme of the present invention, the waterborne polyurethane slurry is prepared from the following components by mass: 100 parts of aliphatic waterborne polyurethane, 1-1.5 parts of leveling agent, and 5-8 parts of curing agent. It should be noted that in the present invention, the preparation of the waterborne polyurethane slurry is not particularly limited, and those skilled in the art can select it according to actual conditions. The curing agent of the waterborne polyurethane slurry can be selected from at least one of polycarbodiimide crosslinking agents and isocyanate crosslinking agents, and the leveling agent can be selected from polyether-modified siloxane.

[0021] The present invention also provides an application of the aforementioned non-weakening polyurethane composite material or the non-weakening polyurethane composite material prepared by the aforementioned preparation method in automobile interior decoration.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The polyurethane high-solid adhesive layer of the present invention forms a three-dimensional network cross-linked structure by reacting a reactive polyurethane prepolymer with a cross-linking agent and a filler in a certain proportion, so that the film has a certain strength and brittleness, thereby achieving an overall brittle fracture of the non-weakened polyurethane composite material under the impact of the explosive force, thereby ensuring the safe deployment of the airbag.

[0024] 2. In the polyurethane high-solid adhesive layer of the present invention, the reactive polyurethane prepolymer is an aliphatic isocyanate prepolymer. The excess -NCO groups in the reactive polyurethane prepolymer can react with the active hydrogen groups on the surface of the base fabric to form strong urethane bonds (-NH-COO-) and urea bonds (-NH-CONH-), thereby achieving good adhesion between the polyurethane high-solid adhesive layer and the base fabric. Through a thinner polyurethane high-solid adhesive layer, good adhesion to the base fabric can be achieved, thereby reducing the weight of the product.

[0025] 3. The surface layer and adhesive layer of the present invention are all aliphatic structures without benzene ring structure, which improves the light degradation resistance of automobile interior. In addition, the base fabric is still made of polyester base fabric with good heat resistance and strength, which ensures the durability of the weakening-free material in automobile interior application as a whole.

[0026] 4. Compared with the traditional weakening method, the non-weakening polyurethane composite material of the present invention does not need a thicker adhesive layer to reduce the loss of aesthetics caused by weakening. Therefore, the thickness of the non-weakening leather adhesive layer is thinner and the weight is lighter. In addition, the non-weakening base fabric layer uses a mesh fabric with a lighter weight. The overall weight of the product is reduced by about 20%, which improves the energy economy and power performance of the car.

[0027] 5. The present invention reduces the weakening process, reduces the cost of post-processing, and improves the aesthetics of the product. DETAILED DESCRIPTION

[0028] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0029] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0030] The raw material information used in the above examples and comparative examples is as follows:

[0031] (1) Polyurethane resin LY-58PC (aliphatic polycarbonate polyurethane, 100% modulus 4.5±1.0 MPa) and reactive isocyanate prepolymer PU-28 (aliphatic, NCO content 5%) were both sourced from Hefei Anli Polyurethane New Materials Co., Ltd.

[0032] (2) Solvent-free polyether polyurethane Haptex CC 6945 / 100C-A, Haptex CC 6945 / 100C-B, and solvent-free catalyst Additive CX 93600 are all from BASF Polyurethane Specialties (China) Co., Ltd.;

[0033] (3) NX-128 was purchased from Nantong Advant Co., Ltd.;

[0034] (4) Cross-linking agent HMDA was purchased from Hubei Jusheng Technology Co., Ltd.;

[0035] (5) Cross-linking agent MTHPA was purchased from Kunshan Jiulimei Electronic Materials Co., Ltd.;

[0036] (6) Color paste was purchased from Foshan Shunde Baoster Pigment Co., Ltd.;

[0037] (7) Filler: antimony trioxide, purchased from Hunan Xikuangshan Shanxing Antimony Industry Import and Export Co., Ltd.

[0038] (8) Filler: calcium carbonate, purchased from Jiangxi Darui Chemical Co., Ltd.;

[0039] (9) Polycarbonate waterborne polyurethane WF-3649 was purchased from Starr Fine Coatings (Suzhou) Co., Ltd.;

[0040] (10) Curing agent XR-5580 and leveling agent LA-91-120 were purchased from Starr Fine Coatings (Suzhou) Co., Ltd.;

[0041] (11) Mesh fabric B30D0087 and weft knitted fabric PK280 were purchased from Jiangsu Beltfor New Materials Co., Ltd.;

[0042] (12) Polylactic acid base fabric PLA-1 was purchased from Zhangjiagang Jimei Biotechnology Co., Ltd.

[0043] The above raw materials can all be obtained commercially. The above raw materials are only for illustrating the sources and components of the reagents used in the experiments of the present invention so as to fully disclose the information. It does not mean that the present invention cannot be achieved by using other similar reagents or reagents provided by other suppliers.

[0044] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the present technical field.

[0045] Example 1

[0046] This embodiment provides a weakening-free polyurethane composite material for automobile interior, which includes a polyurethane surface layer, a polyurethane high-solid bonding layer, and a base fabric layer arranged in sequence from top to bottom. The preparation method thereof includes the following four steps S1-S4.

[0047] S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 10 threads, place it at 140°C for 2 minutes, and dry it to form a polyurethane surface layer. The surface polyurethane slurry is prepared from the following raw materials by weight: 150 parts of aliphatic polyurethane resin LY-58PC, 50 parts of N,N-dimethylformamide, and 5 parts of color paste.

[0048] S2. Coat the polyurethane high solid adhesive layer slurry on the polyurethane surface layer with a knife head gap of 30 threads, and bake it at 140°C for 2 minutes to form a polyurethane high solid adhesive layer. The polyurethane high solid adhesive layer slurry is prepared from the following raw materials in parts by weight: 100 parts of PU-28, 5 parts of crosslinking agent HMDA, 20 parts of antimony trioxide, and 5 parts of color paste.

[0049] S3, the mesh cloth B30D0087 and the polyurethane high solid adhesive layer are laminated with a lamination gap of 60 threads, and dried to obtain a weakening-free polyurethane composite material.

[0050] S4. Use a roller coating process to coat the surface of the non-weakening polyurethane composite material with water-based polyurethane slurry, treat it at 160°C for 6 minutes and dry it to form a surface treatment layer, and obtain a non-weakening polyurethane composite material for automotive interior. The water-based polyurethane slurry is prepared from the following raw materials by weight: 100 parts of aliphatic water-based polyurethane WF-3649, 0.5 parts of leveling agent LA-91-120, and 3 parts of curing agent XR 5580.

[0051] Example 2

[0052] This embodiment provides a weakening-free polyurethane composite material for automobile interior, which includes a polyurethane surface layer, a polyurethane high-solid bonding layer, and a base fabric layer arranged in sequence from top to bottom. The preparation method thereof includes the following four steps S1-S4.

[0053] S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 15 threads, place it at 120°C for 1.5 minutes, and dry it to form a polyurethane surface layer. The surface polyurethane slurry is prepared from the following raw materials by weight: 150 parts of aliphatic polyurethane resin LY-58PC, 30 parts of N,N-dimethylformamide, and 7.5 parts of color paste.

[0054] S2. Coat the polyurethane high solid adhesive layer slurry on the polyurethane surface layer with a knife gap of 35 threads, and bake at 125°C for 1.5 minutes to form a polyurethane high solid adhesive layer. The polyurethane high solid adhesive layer slurry is prepared from the following raw materials in parts by weight: 100 parts of PU-28, 7.5 parts of crosslinking agent HMDA, 35 parts of antimony trioxide, and 7.5 parts of color paste.

[0055] S3, the mesh cloth B30D0087 and the polyurethane high solid adhesive layer are laminated with a lamination gap of 70, and dried to obtain a weakening-free polyurethane composite material.

[0056] S4. Use a roller coating process to coat the surface of the non-weakening polyurethane composite material with water-based polyurethane slurry, treat it at 140°C for 4.5 minutes and dry it to form a surface treatment layer, and obtain a non-weakening polyurethane composite material for automotive interior. The water-based polyurethane slurry is prepared from the following raw materials by weight: 100 parts of aliphatic water-based polyurethane WF-3649, 0.75 parts of leveling agent LA-91-120, and 4 parts of curing agent XR 5580.

[0057] Example 3

[0058] This embodiment provides a weakening-free polyurethane composite material for automobile interior, which includes a polyurethane surface layer, a polyurethane high-solid bonding layer, and a base fabric layer arranged in sequence from top to bottom. The preparation method thereof includes the following four steps S1-S4.

[0059] S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 20 threads, place it at 100°C for 1 minute, and dry it to form a polyurethane surface layer. The surface polyurethane slurry is prepared from the following raw materials by weight: 150 parts of aliphatic polyurethane resin LY-58PC, 10 parts of N,N-dimethylformamide, and 10 parts of color paste.

[0060] S2. Coat the polyurethane high solid adhesive layer slurry on the polyurethane surface layer with a knife gap of 40 threads, and bake it at 110°C for 1 minute to form a polyurethane high solid adhesive layer. The polyurethane high solid adhesive layer slurry is prepared from the following raw materials in parts by weight: 100 parts of PU-28, 10 parts of crosslinking agent HMDA, 50 parts of antimony trioxide, and 10 parts of color paste.

[0061] S3, bonding the mesh cloth B30D0087 and the polyurethane high solid adhesive layer with a lamination gap of 80, and drying to obtain a weakening-free polyurethane composite material.

[0062] S4. Use a roller coating process to coat the surface of the non-weakening polyurethane composite material with water-based polyurethane slurry, treat it at 120°C for 3 minutes and dry it to form a surface treatment layer, and obtain a non-weakening polyurethane composite material for automotive interior. The water-based polyurethane slurry is prepared from the following raw materials by weight: 100 parts of aliphatic water-based polyurethane WF-3649, 1.5 parts of leveling agent LA-91-120, and 5 parts of curing agent XR 5580.

[0063] Example 4

[0064] This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that in this embodiment, the polyurethane high solid bonding layer slurry is prepared from the following raw materials in parts by mass: 100 parts of PU-28, 5 parts of cross-linking agent MTHPA, 20 parts of antimony trioxide, and 5 parts of color paste.

[0065] Example 5

[0066] This embodiment adopts the same implementation method as Example 1, and the difference from Example 1 is that in this embodiment, the polyurethane high solid bonding layer slurry is prepared from the following raw materials in parts by weight: 100 parts of PU-28, 5 parts of cross-linking agent MTHPA, 20 parts of calcium carbonate, and 5 parts of color paste.

[0067] Comparative Example 1

[0068] This comparative example proposes a conventional weakened polyurethane composite material for automobile interior, which includes a polyurethane surface layer, a solvent-free adhesive layer, and a base fabric layer arranged in sequence from top to bottom, and its preparation method includes the following four steps S1-S4.

[0069] S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 20 threads, place it at 100°C for 1 minute, and dry it to form a polyurethane surface layer. The surface polyurethane slurry is prepared from the following raw materials by weight: 150 parts of aliphatic polyurethane resin LY-58PC, 10 parts of N,N-dimethylformamide, and 10 parts of color paste.

[0070] S2. Coat the solvent-free adhesive layer slurry on the polyurethane surface layer with a knife head gap of 45 wires, and bake it at 120°C for 1 minute to form a solvent-free adhesive layer. The solvent-free adhesive layer slurry is prepared by mixing the polyether polyol combination A material and the aromatic Haptex CC 6945 / 100C-B in a mass ratio of 100:70, and the polyether polyol combination A material is prepared from the following raw materials in mass parts: 100 parts of Haptex CC 6945 / 100C-A, 20 parts of antimony trioxide, 0.4 parts of NX-128 and 0.15 parts of Additive CX 93600.

[0071] S3. The high-density weft-knitted fabric PK280 and the solvent-free adhesive layer are laminated with a lamination gap of 80 threads, and dried to obtain a conventional weakened automotive interior polyurethane composite material.

[0072] S4. Use a roller coating process to coat the surface of the automotive interior polyurethane composite material with water-based polyurethane slurry, treat it at 120°C for 3 minutes and dry it to form a surface treatment layer, and obtain a non-weakening polyurethane composite material for automotive interior. The water-based polyurethane slurry is prepared from the following raw materials by weight: 100 parts of aliphatic water-based polyurethane WF-3649, 1.5 parts of leveling agent LA-91-120, and 5 parts of curing agent XR 5580.

[0073] Comparative Example 2

[0074] This comparative example adopts the same implementation as comparative example 1, and the difference from comparative example 1 is that in this comparative example, the base fabric layer adopts left-handed polylactic acid base fabric PLA-1.

[0075] Comparative Example 3

[0076] This comparative example adopts the same implementation as Example 3, and the difference from Example 3 is that in this comparative example, the HMDA in the polyurethane high solid adhesive layer slurry is 15 parts.

[0077] Test Case

[0078] The finished products of the non-weakening polyurethane composite materials for automobile interior decoration of the above embodiments and comparative examples were subjected to performance tests, and the test results are shown in Table 1.

[0079] Table 1 Performance of the finished products of the non-weakening polyurethane composite materials for automobile interior decoration of the embodiments and comparative examples

[0080]

[0081] From the results in Table 1, we can see that:

[0082] The polyurethane composite materials prepared in Examples 1-5 of the present invention have certain advantages in appearance and light weight compared with the polyurethane composite materials prepared in Comparative Example 1, which shows that the structural design of the polyurethane high-solid adhesive layer of the present application can not only improve the aesthetic appearance, but also improve the energy consumption economy and power performance of the automobile;

[0083] The polyurethane composite materials prepared in Examples 1-5 of the present invention have excellent heat resistance and light resistance compared with the polyurethane composite material prepared in Comparative Example 2, which shows that the use of low-density polyester knitted mesh fabric in the present application can improve the heat resistance and light resistance of the polyurethane composite material;

[0084] The polyurethane composite materials prepared in Examples 1-5 of the present invention have excellent peel strength and blasting effect compared with the polyurethane composite materials prepared in Comparative Example 3, which indicates that the polyurethane high-solid bonding layer and the base fabric of the present application can undergo overall brittle fracture under the impact of the explosive force, and the airbag can be safely deployed, ensuring the reliability of the safety function.

[0085] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0086] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A weakening-free polyurethane composite material, characterized in that: It includes a polyurethane surface layer, a polyurethane high-solid bonding layer, and a base fabric layer which are arranged in sequence from top to bottom; The polyurethane high-solid adhesive layer is prepared from a polyurethane high-solid adhesive layer slurry, and the polyurethane high-solid adhesive layer slurry is prepared from the following components in parts by weight: 100 parts of reactive polyurethane prepolymer, 5-10 parts of crosslinking agent, 20-50 parts of filler, and 5-10 parts of color paste.

2. The weakening-free polyurethane composite material according to claim 1, characterized in that: The reactive polyurethane prepolymer is an aliphatic isocyanate prepolymer, with a solid content of 100% and a free NCO content of 4.5%±1%.

3. The weakening-free polyurethane composite material according to claim 1, characterized in that: The cross-linking agent is one of aliphatic amine cross-linking agents, acid anhydrides and polyamides.

4. The weakening-free polyurethane composite material according to claim 1, characterized in that: The filler is at least one of diatomaceous earth, powdered calcium carbonate, aluminum hydroxide, halogen flame retardant and phosphorus flame retardant.

5. The weakening-free polyurethane composite material according to claim 1, characterized in that: The polyurethane surface layer is prepared from polyurethane surface layer slurry, and the polyurethane surface layer slurry is prepared from the following components in parts by weight: 150 parts of aliphatic polyurethane resin, 10-50 parts of N,N-dimethylformamide, and 5-10 parts of color paste.

6. The weakening-free polyurethane composite material according to claim 1, characterized in that: The base fabric layer is a low-density polyester knitted mesh fabric, and the tear strength of the base fabric layer is 10-25N / 3cm.

7. A method for preparing the weakened-free polyurethane composite material according to any one of claims 1 to 6, characterized in that: It includes the following steps: S1. Coat the polyurethane surface slurry on the release paper with a knife gap of 10-20 threads, place it at 100-140℃ for 1-2min, and dry it to form a polyurethane surface layer; S2. A polyurethane high solid resin slurry is coated on the polyurethane surface layer with a cutter gap of 30-40 wire, and is dried at 110-140 ℃ until semi-dry to form a polyurethane high solid adhesive layer; S3. Laminating the base fabric and the polyurethane high-solid adhesive layer with a lamination gap of 60-80 mm, and drying to obtain a weakening-free polyurethane composite material.

8. The method for preparing the weakening-free polyurethane composite material according to claim 7, characterized in that: The method for preparing the weakening-free polyurethane composite material further comprises the following steps: S4. After coating the water-based polyurethane slurry on the surface of the non-weakening polyurethane composite material with a roller coating process, treating it at 130-160° C. for 2-5 minutes, and drying it, a surface treatment layer is formed on the surface of the non-weakening polyurethane composite material.

9. The method for preparing the weakening-free polyurethane composite material according to claim 8, characterized in that: The waterborne polyurethane slurry is prepared from the following components in parts by mass: 100 parts of aliphatic waterborne polyurethane, 1-1.5 parts of a leveling agent, and 5-8 parts of a curing agent.

10. Use of the non-weakening polyurethane composite material according to any one of claims 1 to 6 or the non-weakening polyurethane composite material prepared by the preparation method according to any one of claims 7 to 9 in automobile interior decoration.

Citation Information

Patent Citations

  • Weakening-free PU instrument board leather, preparation method thereof and instrument board

    CN114673014A

  • Polyurethane composite material with high light resistance as well as preparation method and application thereof

    CN117656637A

  • Laminate and skin material of vehicle interior material

    JP2020044707A

  • Method for producing skin material for interior material of automobile and skin material for interior material of automobile using the same

    KR1020170071026A

  • Elastomeric composite polyurethane skins

    US20200032017A1

Cited By

  • Weakening-free PVC (polyvinyl chloride) automotive interior leather and preparation method thereof

    CN120792267A

  • Non-embrittled PVC automotive interior leather and method for producing the same

    CN120792267B